2006
DOI: 10.1139/g06-053
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of the mitochondrial DNA control region in Aedes aegypti

Abstract: The complete A+T - rich region of Aedes aegypti mitochondrial DNA has been cloned and sequenced. In Argentinean populations of the species, a polymorphism in the length of the amplified fragment was observed. Nucleotide sequence comparison of the shortest and longest A+T - rich amplified fragments detected revealed the presence of 2 types of tandemly repeated blocks. The size variation observed in natural populations is mainly due to the presence of a variable number of a 181 bp tandem repeat unit, located tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This mitogenome sequence confirmed that the A. albopictus control region belongs to group 2 of insect control regions (Zhang and Hewitt, 1997), like that of A. aegypti (Dueñas et al, 2006). Three conserved blocks are positioned along the region, which contains two different types (I and II) of tandem repeats ( Figure 2 ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This mitogenome sequence confirmed that the A. albopictus control region belongs to group 2 of insect control regions (Zhang and Hewitt, 1997), like that of A. aegypti (Dueñas et al, 2006). Three conserved blocks are positioned along the region, which contains two different types (I and II) of tandem repeats ( Figure 2 ).…”
Section: Resultssupporting
confidence: 65%
“…Black diamonds represent in the order from left to right: a poly-T stretch motif, a poly-T stretch motif followed by a GC-rich block, and a short poly-A stretch motif. All of these are conserved in different mosquito species (Dueñas et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…The MLEs for the F84 nucleotide substitution model parameters suggested unequal base frequencies in line with observations from mtDNA of insects and Ae. aegypti (Dueñas et al. 2006; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The MLEs for the F84 nucleotide substitution model parameters suggested unequal base frequencies in line with observations from mtDNA of insects and Ae. aegypti (Dueñas et al 2006; Table S3). Across sampling scales, differences in base frequency MLEs were on the order of 10 )3 and were considered too small to be reported.…”
Section: Descriptive Statistics and Tests Of Assumptionsmentioning
confidence: 99%
“…The length of the A+T-rich region ranges from tens to several thousands of base pairs (Lewis et al 1995;Shao et al 2001). It is one of the most variable regions of mtDNA, not only because of its high rates of nucleotide substitution and insertions/ deletions, but also because of the presence of varying copy numbers of tandemly repeated elements (Zhang and Hewitt 1997;Duenas et al 2006). The structural organization of the insect mtDNA A+T-rich region (also known as the control region) has been studied extensively (Zhang et al 1995;Zhang and Hewitt 1997;Duenas et al 2006;Cha et al 2007).…”
Section: Introductionmentioning
confidence: 99%